Institutional Repositories: an Internal and External Perspective on the Value of IRs for Researchers’ Communities - Cassella, Maria (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Institutional repositories represent extremely innovative technology, but repository managers still struggle to bring together a critical mass of content and to demonstrate their overall impact on research. In this paper I propose a set of Performance Indicators (PIs) to assess institutional repositories’ success. Fourteen internal indicators are selected and inserted in the quadruple ‘balanced scorecard’ perspective. Three more indicators from an external perspective are then proposed and discussed by the author. I hope that this study will foster the development of standard Performance Indicators for IRs in the very near future, in order to help IR managers to demonstrate their repositories’ cost-effectiveness and success.